Integrasi Nilai-Nilai Religius dalam Pembentukan Karakter: Perspektif Psikologi Agama - Rofiqul Anam (Jurnal At-Tadbir : Media Hukum dan Pendidikan, 2026)
This study aims to analyze the role of the psychology of religion in shaping individual character and personality through a multidisciplinary approach. The research method employed is library research, analyzing various relevant literature on the psychology of religion, character building, and personality development. The findings reveal that the internalization of religious values such as honesty, empathy, responsibility, and tolerance plays a significant role in shaping individual character. Key factors influencing this process include family environment, religiously-based formal education, involvement in religious communities, wise use of technology, and individuals' intrinsic motivation. The study concludes that integrating religious values can bridge the gap between religious idealism and its practical implementation in daily life, while also making a significant contribution to creating a society characterized by integrity, harmony, and inclusivity.